Implementasi Sistem Informasi Akuntansi dalam Meningkatkan Akuntanbilitas Laporan Keuangan pada UMKM Kerupuk Azizah Kota Padang - Wilfah Busri Wahyu; Hayu Yolanda Utami; Teguh Hidayat; Zulkifli (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program aimed to implement an Accounting Information System (AIS) based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) at Kerupuk Azizah MSME in Padang City to improve financial reporting accountability. The program employed observation, needs assessment, training, implementation assistance, and evaluation through discussions and post-tests. The results showed improved participants’ competence in preparing SAK EMKM-compliant financial statements, calculating production costs, managing inventory, and utilizing financial information for decision-making. The program outputs included a Microsoft Excel-based bookkeeping system, SAK EMKM-compliant financial reporting templates, and a user guide to support sustainable implementation. Evaluation results indicated an 85% level of participant understanding, demonstrating that the AIS effectively enhanced financial reporting accountability and strengthened the professionalism of MSME financial management.